Reformulasi Strategi Menembus Pasar Internasional PT. Berkat Mukmin Mandiri Sidoarjo - Wahyudi, M. Adi Trisna; Mahfudiyanto, Mahfudiyanto; Fahim, M. Thal’at (BISNIS, 2022)
This study aims to reveal the reformulation of strategies in penetrating the international market of PT. Berkat Mukmin Mandiri, Sidoarjo. The type of research used is descriptive qualitative with subjects are commissioners, HRD, Marketing Leaders, employees, government and overseas partners (buyers). The results showed that the role of stakeholders in increasing the coffee export market of PT. Berkat Mukmin Mandiri, among others are expanding the network of foreign partners, establishing business communication between organizations, establishing good relations with the government, always increasing product added value, applying working principles according to sharia principles, using the Blue Ocean strategy, carrying out export promotions, capturing existing market opportunities. and increase export targets, support to increase product added value and develop access to cooperation with foreign parties, assist product promotion through CTH (cooperative trading house), as a medium that helps exports and helps find markets in their country. Then the results of the SWOT analysis show that the right strategy in increasing the coffee export market of PT. Berkat Mukmin Mandiri is an SO (Strength – Opportunity) strategy, which is a strategy by utilizing strength as a tool to seize as many opportunities as possible.